Error Analysis on the Use of Letters in Indonesian Paper Written By Thai Student - Susrina Kalee; Yumna Rasyid; Liliana Muliastuti (English Department - University of Sultan Ageng Tirtayasa, 2018)
This study aimed to describes the form of errors of using letters that found in Indonesian paper made by Thai students. The data in this study were words and sentences that contained errors. The research is a qualitative research using content analysis method. This research used model data analysis of James, through four steps, first Elicitation and Registration, second Error Identification, third categorizing the errors and the last Diagnosis. The results show that there are 118 errors of using letters: 1) capital letters there are 54 or48% errors, 2) italic there are 23 or 19% errors, and 3) bold there are 35 or 35% errors. The error is caused by ignorance of rule restriction of intralingual factor was 118 or 100% errors. However, the results of the study showed that students have not mastered or understand the structure of Indonesian Language. The results of this study can be used to develop the techniques of teaching Indonesian structure, especially in the field of use letters so; students could improve the ability of using Indonesian language that will be poured into academic writing properly and correctly. Keyword: error analysis, the use of letters, Indonesian language